Pa'k and Prejudice: Theme of Swan and Woman’s Purity in Ongarsynova’s and Makatayev’s Poetry - Kanatova, Aigerim (Nazarbayev University School of Sciences and Humanities, 2020)
This project is analyzing the women’ position in Kazakhstan by looking at Fariza Ongarsynova’s and Mukagali Makatayev’s poems written in 1960-1980s. Four poems on two interconnected topics are selected to be analyzed in this paper: the purity of women and the swan. The beauty and purity of the swan is frequently associated with the same features in women for several reasons. Kazakh society’s attitude towards women is also mirrored in their cultural beliefs towards swans. It treats swans as sacred birds due to their fidelity and white color which personifies purity. The issue with virginity and purity, the harassment and prejudice of the society towasrds the behavior of women and how they were treated can be clearly seen in Fariza’s works. A different pattern could be found in Makatayev’s poetry: the use of the term “пәк” (purity), but in a different approach. This paper is going to analyze how the same term for the purity of women can be understood and used differently between the male and female Kazakh writers. In Ongarsynova’s poems, the feelings of frustration, pain and at the same time rebellion are expressed, whereas in Makatayev’s poems the same actions have a joyful character. One of the main questions so far of my project is: “What are the factors that contribute to the different attitude between female and male writers towards Kazakh women?”. In order to answer this question, the paper proposes a close reading of four poems, studies the letters and interviews by these writers and analyze the secondary literature written about the Kazakh poetry and women at that time.
Keywords: Kazakh poetry, Makatayev, Ongarsynova, virginity, image of the swan